The Role of Buddhist Philosophy in Aldous Huxley’s „Island” - Warchał, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
Aldous Huxley’s last novel, „Island”, presents the utopian, peaceful society of Pala, a secluded island in the Pacific Ocean. Selected principles of Mahayana Buddhism constitute the cornerstone of Pala’s political, educational and agricultural systems and serve as the main source of moral values for its inhabitants. By introducing characters who represent both Palanese and Western mentality, the author presents the clash of Western and Eastern cultures and, as a result, unmasks the destructiveness of Western greed, materialism and militarism. Moreover, the novel constitutes a reflection upon the spiritual and intellectual benefits of Buddhism, as it presents the peaceful coexistence of the inhabitants of Pala and their pursuit of self-improvement, knowledge and spiritual enlightenment. The following paper aims to confront the views and attitudes of characters who represent the East and the West as well as to trace Buddhist motifs in Huxley’s novel in order to examine their role both in all aspects of Pala’s culture and in the philosophical message of „Island”.
Keywords: Aldous Huxley; Island; Mahayana Buddhism; the East and the West; utopian novel